أهمية التحضير النفسي للاعبي كرة القدم خلال المنافسة الرياضية لأقل من 17سنة - شعلان شكري (My University, 2023)
The summary of the survey  Title of the Study: The Importance of Psychological Preparation for Football Players during Competition for players under 17 years (case study of ESSA)  Purpose of the Study: studying the importance of psychological preparation on Football Players during Competition for players under 17 years (case study of ESSA)  Statement of the problem: What is the importance of the psychological preparation for Football Players during Sports Competition for players under 17 years?  Hypothesizes of the study: 1. What is the effect of psychological preparation in remaining the players’ focus and attention during competition? 2. Does the importance of psychological preparation lie in limiting the players’ anxiety and stress during competition? 3. How much attention do football players give to Psychological Preparation during Competition?  Research Methodology: Descriptive approach Research  Population: 24 players (non-random population)  Theoretical Background: it includes the definition of sports psychology, sports competition, football, adolescence.  Research Tools:  Arabic an Foreign sources  Personal interviews  Questionnaires  The Found Results: Psychological Preparation has an enormous importance on football players whom aged less than 17 years old during sports competition.  Important recommendations and Future Prospects:  Taking into account the psychological characteristics of the age group and the psychological pressures that the player is exposed to.  Using the finest methods and means to adopt excellent psychological preparation ways methods.  Football coaches should pay great attention to psychological preparation for especially under 17-year-olds players  Theoretical background: This includes the concept of sports psychology, psychological preparation, sports competition, football, adolescence.  The definition of sports psychology: it explains the importance of the psychological preparation physically and mentally.  Psychological preparation: It includes the importance of the psychological preparation and its roles.  Sports Competition: it covers the types of sports competition and their theories.  Football: it gives a historical review on football, the requirements of modern football, and the characteristics of a football player.  Adolescence: it discusses the definition of Adolescence and its characteristics.  Literature Review: The Practical Chapter: it includes 2 parts: 1/ research methodology: It addressed multiple methodological steps to conduct scientific researches. 2/ presentation and the analysis of results: the results were collected, analyzed, and discussed ......................................................................ملخص الدراسة.......................................................................................  عنوان الدراسة: أهمية التحضير النفسي للاعبي كرة القدم خلال المنافسة الرياضية لأقل من 17 سنة – (دراسة ميدانية لنادي وفاق سوق أهراس).  هدف الدراسة: دراسة أهمية التحضير النفسي للاعبي كرة القدم خلال المنافسة الرياضية لأقل من 17 سنة – دراسة ميدانية على مستوى نادي وفاق – سوق أهراس-  مشكلة الدراسة: أين تكمن أهمية التحضير النفسي للاعبي كرة القدم خلال المنافسة الرياضية لأقل من 17 سنة؟  فرضيات الدراسة: 1- الفرضية العامة: للتحضير النفسي للاعبي كرة القدم لأقل من 17سنة أهمية كبيرة خلال المنافسة الرياضية 2- الفرضيات الجزئية:  ما مدى تأثير التحضير النفسي في المحافظة على التركيز وانتباه لاعبي كرة القدم خلال المنافسة الرياضية؟  هل أهمية التحضير النفسي تكمن في الحد من القلق والتوتر لدى لاعبي كرة القدم خلال المنافسة الرياضية؟  ما مدى الاهتمام الذي يوليه لاعبي كرة القدم للتحضير النفسي خلال المنافسة الرياضية؟  عينة الدراسة: عينة قصدية متمثلة في فريق وفاق سوق أهراس متكونة من 24 لاعب.  المنهج المتبع في الدراسة: المنهج الوصفي.  أدوات الدراسة:  المصادر العربية و الأجنبية.  المقابلات الشخصية.  الاستبيان.  النتائج المتوصل إليها: للتحضير النفسي أهمية كبيرة للاعبي كرة القدم خلال المنافسة الرياضية لأقل من 17سنة.  أهم الاقتراحات و الأفاق المستقبلية:  مراعاة الخصائص النفسية للمرحلة العمرية والضغوطات النفسية التي يتعرض لها اللاعب.  استعمال أفضل الطرق والوسائل وانتهاج أحسن السبل في التحضير النفسي.  وجب على مدربي كرة القدم خاصة فئة أقل من 17سنة الاهتمام بالتحضير النفسي.  الخلفية النظرية: والذي يضم مفهوم علم النفس الرياضي، التحضير النفسي، المنافسة الرياضية، كرة القدم، المراهقة.  مفهوم علم النفس الرياضي: تطرقنا فيه إلى أهمية علم النفس الرياضي من الناحية البدنية والنفسية....  التحضير النفسي: تطرقنا فيه إلى أهمية التحضير النفسي دوره ومهامه...  المنافسة الرياضية: تطرقنا فيه إلى أنواع المنافسة الرياضية وأبعادها، ونظرياتها...  كرة القدم: تناولنا فيه نبذة تاريخية عن كرة القدم، متطلبات كرة القدم الحديثة، صفات لاعب كرة القدم...  المراهقة: تناولنا فيه المراهقة واهم خصائص الفئة العمرية...  الدراسات السابقة والمشابهة: تمثلت في 04 دراسات تم التعليق علها والاستفادة منها الجانب التطبيقي: والذي ضم جانبين: الإجراءات المنهجية للبحث: تم التطرق فيه إلى جميع الخطوات المنهجية لإعداد البحوث العلمية. عرض وتحليل النتائج: تم فيه جمع النتائج ومعالجتها ثم تحليلها ومناقشها ...................................................................................résumer................................................................................................... Titre de l’étude : L’importance de la préparation mentale des joueurs de football de moins de 17 ans pendant la compétition sportive – Une étude de terrain pour le club WAFA Souk Ahras. Objectif de l’étude : Étudier l’importance de la préparation mentale des joueurs de football de moins de 17 ans pendant la compétition sportive – Étude de terrain au niveau du club WAFA – Souk Ahras. Problème de l’étude : Où réside l’importance de la préparation mentale des joueurs de football de moins de 17 ans pendant la compétition sportive ? Hypothèses de l’étude : Hypothèse générale : La préparation mentale des joueurs de football de moins de 17 ans est d’une grande importance pendant la compétition sportive. Hypothèses spécifiques : Dans quelle mesure la préparation mentale affecte-t-elle la concentration et l’attention des joueurs de football pendant la compétition sportive ? L’importance de la préparation mentale réside-t-elle dans la réduction de l’anxiété et du stress chez les joueurs de football pendant la compétition sportive ? Dans quelle mesure les joueurs de football accordent-ils d’importance à la préparation mentale pendant la compétition sportive ? Échantillon de l’étude : Un échantillon intentionnel composé de 24 joueurs de l’équipe WAFA Souk Ahras. Méthodologie de l’étude : Méthode descriptive. Outils de l’étude : Sources arabes et étrangères. Entretiens individuels. Questionnaire. Résultats obtenus : La préparation mentale est d’une grande importance pour les joueurs de football de moins de 17 ans pendant la compétition sportive. Principales suggestions et perspectives futures : Tenir compte des caractéristiques psychologiques de la tranche d’âge et des pressions psychologiques auxquelles les joueurs sont exposés en utilisant les meilleures méthodes et moyens et en adoptant la meilleure approche en matière de préparation mentale. Les entraîneurs de football, en particulier pour la catégorie des moins de 17 ans, doivent accorder une attention particulière à la préparation mentale. Contexte théorique comprenant le concept de psychologie sportive, la préparation mentale dans le sport, le football, l’adolescence. Nous avons abordé l’importance de la psychologie sportive du point de vue physique et mental
دراسة ميدانية على النادي الرياضي الهاوي لوفاق سوق أهراس